Surviving and thriving with an invisible chronic illness : how to stay sane and live one step ahead of your symptoms - Jacqueline, Ilana (New Harbinger Publications, Inc., 2018)
"Popular blogger Ilana Jacqueline writes poignantly about living with two debilitating autoimmune diseases and presents advice and practical tips for living with an invisible chronic illness. Do you live with a chronic, debilitating, yet invisible condition? You may feel isolated, out of step, judged, lonely, or misunderstood--and that's on top of dealing with the symptoms of your actual illness. Take heart. You are not alone, although sometimes it can feel that way. Written by a blogger who suffers from two autoimmune diseases, Surviving and Thriving with an Invisible Chronic Illness offers peer-to-peer support to help you stay sane, be your own advocate, and get back to living your life. This smart, compelling guide is written for anyone suffering with an illness no one can see--such as postural orthostatic tachycardia syndrome (POTS), chronic fatigue syndrome (CFS), fibromyalgia, multiple chemical sensitivity (MCS), Lyme disease, lupus, dysautonomia, or even multiple sclerosis (MP). This book will tell you everything you need to know about living with a complicated, invisible condition--from how to balance sex, dating, and relationships to handling work and school with unavoidable absences. You'll also learn to navigate judg-y or skeptical relatives and strangers and--most importantly--manage your medical care. Suffering from a chronic illness doesn't mean you can't live an active, engaged life. This book will show you how"--